Severe hypertriglyceridemia in a patient heterozygous for a lipoprotein lipase gene allele with two novel missense variants - Kassner, Ursula; März, Winfried (European journal of human genetics, 2015)
Rare monogenic hyperchylomicronemia is caused by loss-of-function mutations in genes involved in the catabolism of triglyceride-rich lipoproteins, including the lipoprotein lipase gene, LPL. Clinical hallmarks of this condition are eruptive xanthomas, recurrent pancreatitis and abdominal pain. Patients with LPL deficiency and severe or recurrent pancreatitis are eligible for the first gene therapy treatment approved by the European Union. Therefore the precise molecular diagnosis of familial hyperchylomicronemia may affect treatment decisions. We present a 57-year-old male patient with excessive hypertriglyceridemia despite intensive lipid-lowering therapy. Abdominal sonography showed signs of chronic pancreatitis. Direct DNA sequencing and cloning revealed two novel missense variants, c.1302A>T and c.1306G>A, in exon 8 of the LPL gene coexisting on the same allele. The variants result in the amino-acid exchanges p.(Lys434Asn) and p.(Gly436Arg). They are located in the carboxy-terminal domain of lipoprotein lipase that interacts with the glycosylphosphatidylinositol-anchored HDL-binding protein (GPIHBP1) and are likely of functional relevance. No further relevant mutations were found by direct sequencing of the genes for APOA5, APOC2, LMF1 and GPIHBP1. We conclude that heterozygosity for damaging mutations of LPL may be sufficient to produce severe hypertriglyceridemia and that chylomicronemia may be transmitted in a dominant manner, at least in some families.